Cultural Transformation of Ex-PLA in Nepal: A Case Study of Kailali District - Adhikari, Kanshi Prasad (Academia Research Journal, 2022)
This study examined how the cultural values of Ex-PLA have changed along with their social position. This research seeks to investigate the three conditions of Ex-PLA: before, being, and after the war; and its integration. The objective of the research was to examine how cultural values of Ex-PLAs have changed in their time phases. When Ex-PLA has a significant number of settlements, I have picked the field Lamki Chuha Municipality of the Kailali district for this research. Interviews, observations, and a case study were all employed to gather the qualitative data for this study. The conclusion of this study has sought the life experiences of Ex-PLA who switched from being professional Marxists to becoming cultural one for adjustment in society. The research is significant for the Moist Party, the government of Nepal, and non-governmental organizations to get information which will be useful in formulating policy.